MEWUJUDKAN PENEGAKAN HUKUM YANG BAIK DI NEGARA HUKUM INDONESIA (Dialogia Iuridica, 2019)
The Indonesian Constitution states that Indonesia is a state of law, but what happens today is that the law is not respected. The law will be closely linked with justice, authority, revelation, which in turn creates peace, and rules in the sense of rules that contain the norm. The law has a function to provide protection to human interests (all human beings without exception). Therefore, the law must be implemented so that human interest can be protected. In practice, the law can run normally and peacefully, but there can also be legal violations in practice. In the case of law enforcement that we have done so many people say that law enforcers in Indonesia are still weak and do not understand the law, and law enforcement in Indonesia is still relatively weak. And there are those who say our law enforcement, many fail. In this case law enforcement is a central issue in the rule of law, where law enforcement is a reflection of a country. A good legal state will bring about good law enforcement, so that people feel comfortable within a country of law. This paper explains how law enforcement, carried out in accordance with the rules, and is responsive, thus realizing Indonesia as a state law.